Assessment of global antimicrobial resistance campaigns conducted to improve public awareness and antimicrobial use behaviours: a rapid systematic review - Ellie L. Gilham; Nicola Pearce-Smith; Vanessa Carter; Diane Ashiru-Oredope (BMC, 2024)
Abstract Introduction Public health campaigns with a well-defined outcome behaviour have been shown to successfully alter behaviour. However, the complex nature of antimicrobial resistance (AMR) creates challenges when evaluating campaigns aimed at raising awareness and changing behaviour. Aims To determine what campaigns have been conducted and which reported being effective at improving awareness of antimicrobial resistance and changing behaviour around antimicrobial use in members of the public. It also sought to determine the outcome measures studies have used to assess campaign effectiveness. Methods A systematic search of Ovid MEDLINE and Embase, was conducted in October 2022 using a predefined search strategy. Studies which were published between 2010 and September 2022 that outlined a campaign or invention aimed at the public and focusing on AMR or antibiotic usage were eligible for inclusion and studies which solely targeted healthcare professionals (HCP) were excluded. Results Literature searches retrieved 6961 results. De-duplication and screening removed 6925 articles, five articles from grey literature and reference screening were included, giving a total of 41 studies and 30 unique interventions. There was a distribution of campaigns globally with the majority run in Europe (n = 15) with most campaigns were conducted nationally (n = 14). Campaigns tended to focus on adult members of the public (n = 14) or targeted resources towards both the public and HCPs (n = 13) and predominately assessed changes in knowledge of and/or attitudes towards AMR (n = 16). Campaigns where an improvement was seen in their primary outcome measure tended to use mass media to disseminate information, targeted messaging towards a specific infection, and including the use of HCP-patient interactions. Discussion This review provides some evidence that campaigns can significantly improve outcome measures relating to AMR and antibiotic usage. Despite a lack of homogeneity between studies some common themes emerged between campaigns reported as being effective. However, the frequent use of observational study designs makes it difficult to establish causation between the campaign and changes seen in the studies outcome measures. It is important that clear evaluation processes are embedded as part of the design process for future campaigns; a campaign evaluation framework for use by campaign developers may facilitate this.